Penambahan Probiotik Dalam Pakan Terhadap Pertumbuhan dan Efisiensi Pakan Benih Ikan Baung (Hemibagrus nemurus) - Muhammad Azwan Fajri; Adelina '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research aimed to determine effect of addition probiotic in artificial feed to growth and retention proteins on fingerling of baung (Hemibagrus nemurus). This research used a completely randomized design (RAL) with one factor, five treatments and 3 replications. The treatment given was different concentrated of probiotic in feed. Consisting of: control (without the addition of probiotic), P1 (addition probiotic of 2 ml/kg feed), P2 (4 ml/kg of feed), P3 (6 ml/kg of feed) and P4 (8 ml/kg of feed). Feed protein content of 28,33%. The results showed addition of probiotic 2, 4, 6, and 8 ml into artificial feed did not give a significant effect (P>0,05) on the feed efficiency, retention of protein, specific growth rate, and survival rate fingerling of baung. The best treatment contained in P4 (8 ml/kg of feed) with 53,92% digestibility of feed, feeding efficiency 26,46%, protein retention 22,43% and the specific growth rate of 2,05%.Keywords: Probiotic, artificial feed, Hemibagrus nemurus